COVID-19 eye infection: recommendations for ophthalmologist and patients - Datu Respatika; Indra Tri Mahayana; Dwi Puspita; Guiddo Ilyasa; Agus Supartoto (Journal of Community Empowerment for Health, 2020)
Coronavirus disease (COVID-19) is a public health emergency of international concern as declared by the World Health Organization on 30 January 2020. Currently, COVID-19 is spreading rapidly worldwide, with no proven treatment nor vaccination, thus infection control measures are paramount. The severity of the majority of COVID-19 cases is mild to moderate, with fever as its most common symptoms, followed by dry cough and fatigue. COVID-19 initially reported to be transmitted from bats but then evolved into human-to-human via droplets. Coronavirus has been detected in tears and conjunctival secretions, but there is still a controversy about whether the virus can be transmitted through tears. However, the ocular transmission might be transported through a lacrimal duct to nasopharyngeal mucosa and then cause an infection. Because the nature of close contact in doctor-patient interaction during ophthalmologic practice, strict measures must be taken to minimize the impact both on the patients and health care workers.